2019
DOI: 10.1186/s42825-019-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Fractionational and structural characterization of lignin and its modification as biosorbents for efficient removal of chromium from wastewater: a review

Abstract: The removal of chromium (Cr) from wastewater by various adsorbents has been investigated. As compared with the commercial activated carbon, the biosorbents with inexpensive and high adsorption capacities are developed from lignocellulosic wastes. Lignin, existing in lignocellulosic biomass, is the second most abundant resource in nature. Recently, lignin-based bio-sorbents were served as an advanced novel material for the metal ions and dye adsorption from wastewater. It has showed several advantages in the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 231 publications
(245 reference statements)
0
28
0
2
Order By: Relevance
“…The physical and chemical properties of lignin produced by content changes of nonpolymeric alcohols in different plant sources are quite different, which is one of the obstacles in industrialization. In the process of plant lignification, the formation of lignin monomer from cross-linking to each other to form lignin macromolecules adds further complexity to the lignin structure [15]. Therefore, the structural complexity of lignin of different species is also an important constraint.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical properties of lignin produced by content changes of nonpolymeric alcohols in different plant sources are quite different, which is one of the obstacles in industrialization. In the process of plant lignification, the formation of lignin monomer from cross-linking to each other to form lignin macromolecules adds further complexity to the lignin structure [15]. Therefore, the structural complexity of lignin of different species is also an important constraint.…”
Section: Introductionmentioning
confidence: 99%
“…[139] They demonstrated that H 2 O 2 production can be increasedb yi ncreasing O 2 production at the anode,w hich is enhanced by increased current density. [139] This increasei nH 2…”
Section: Integrated Electrocatalysis:h 2 O 2 Assistedmentioning
confidence: 89%
“…After separation, lignin is typicallyc ombusted as al ow-grade fuel for its energy value, and for the recovery of pretreatmentc hemicals. [2][3][4] Lignin is the second most abundant biopolymer after cellulose. It is estimated that over 170 billion metric tons of biomass could be annually harvested worldwide, [5] of whichl ignin constitutes 10-25 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam beberapa tahun terakhir, limbah cair yang mengandung ion logam berat telah menyebabkan masalah lingkungan yang serius, terutama yang berkaitan dengan pencemaran tanah (Oyekanmi, et al, 2019a;Oyekanmi, et al, 2019). Lebih memprihatinkan adalah bahwa Cr 3+ yang dibuang berpotensi teroksidasi menjadi kromium heksavalen berbahaya (Cr 6+ ), yang merupakan ancaman bagi kesehatan manusia (Wang, et al, 2019). Keberadaan kromium heksavalen dalam kulit tersamak juga membahayakan kesehatan manusia.…”
unclassified